Image Construction of Islamic Defenders Front in the Jakarta Post Online News - Siti Nurul Hidayah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
This study aimed to observe image construction of the Islamic Defenders Front (FPI) based on six articles of the Jakarta Post Online News about the FPI’s protest toward three issues: Ahmadiyah, the arrival of Lady Gaga in Indonesia, and Ahok as the substitute governor of Jakarta. The author qualitatively explored the FPI’s image using Halliday’s systemic functional linguistics (SFL), which defines the types of process in a clause. The author also analyzed the thematic structure of the clause to support the analysis of each type of process. The result was approximately 208 clauses from the six news articles. This study shows that the dominant process in the above-mentioned three issues is the material process. The material process represents 51% in the issue of Ahmadiyah, 41% in the issue of the arrival of Lady Gaga, and 70% in the issue of Ahok as Jakarta’s substitute governor. This material process shows that the Jakarta Post Online News constructed a negative image of the FPI’s by reporting this organization’s action during the protest. In the issue of Ahmadiyah, the FPI was framed as anarchist, while in the issue of Ahok and of Lady Gaga it was represented as protestor. The analysis of thematic structures shows the FPI as the dominant topical theme, which indicates the FPI was the main topic of the articles.